PENERAPAN METODE MOORA UNTUK MEREKOMENDASI JENIS MAKANAN SEHAT BAGI PENDERITA HIPERTENSI PADA RUMAH SAKIT UMUM DAERAH ABDUL MANAN SIMATUPANG KISARAN - Dwiyanti, Filza; Siddik, Mohd; Parini, Parini (JIPI (Jurnal Ilmiah Penelitian dan Pembelajaran Informatika), 2025)
Hypertension is a high systolic blood pressure of more than 140 mmHg and diastolic blood pressure of more than 90 mmHg on two measurements with an interval of five minutes in a well-rested state. The first rank is hypertension with 12,362 residents. This is also proven by the number of hypertension visits at the Abdul Manan Simatupang Kisaran Regional General Hospital which has continued to increase over the last 2 years. Therefore, it is necessary to carry out preventive efforts in accordance with the health slogan "Prevention is better than cure". Prevention efforts can be done by changing people's diet. In this case, people are required to be more selective in choosing the food they consume. The ability to make decisions quickly, on target and responsibly will be the key to success in global competition in the future. With information technology, it can help users in the process of making accurate and quality decisions with Multi Objective Optimization by Ratio Analysis (MOORA).